Integration of a Bead-Based Immunoassay on a Commercial PCR-Performing POC Device - Benita Johannsen; Desirée Baumgartner; Michal Karpíšek; David Stejskal; Nils Paust; Roland Zengerle; Konstantinos Mitsakakis (Proceedings)
Point-of-care (POC) infectious disease diagnostic devices typically detect either only pathogens or only protein biomarkers, while they provide a low throughput of samples (one to two) tested per run. In this work, we demonstrate the adaptation of a bead-based competitive immunoassay method to be compatible with a commercial POC PCR-performing device without modifications to its hardware. In addition, the assay integration in two half disk-shaped cartridges with seven identical structures on each provides a considerable throughput of 14 samples per 20 min run.